Spatial assessment of environmental fate of Acid Mine Drainage (AMD) contaminants in engineered wetlands along the Varkenslaagte canal - Rampedi, Ike Sephothoma (My University, 2016)
A major cause of environmental problems, in the vicinity of mine tailings in and around Johannesburg, is Acid Mine Drainage (AMD). In most research, engineered wetlands are used to ameliorate AMD with the use of vegetation to remove or extract heavy metals from the soil (i.e. phytoremediation). Phytoremediation has been defined as a technology that uses plants to extract or immobilize contaminants in soils and waters (Torresdey, 2007). The aim of this study was to assess and quantify the mass pool size of contaminants (macronutrients, micronutrients, non-essential trace elements) within and between a subset of paddocks from various compartments including sediments, aboveground biomass (shoots –stems and leaves), and belowground biomass (roots and rhizomes) of the two wetland plant species present (P. australis and S. corymbosus ). Analyses were done on the wetland paddocks in situ and ex situ applying different methods, water sample metal cations were analysed by ICP-MS and the major anion analysis by chromatography and Ion Chromatography (IC). The sediment and plant samples were subject to X-Ray fluorescence (XRF) analyses of major elements and trace elements. Although analysis was undertaken for numerous trace and metal elements, only a few macronutrients, micronutrients, and non-essential elements with significant importance to the West Wits Mining Operation were selected for this study. The stream water test strips yielded poor results for this extremely contaminated plume receiving environment this suggests that in this system they are not a useful substitute for conventional laboratory analyses. Of the elements tested, only S showed significant differences in concentrations in plants between paddocks, with the highest concentrations and mass in the downstream paddocks ww6 and ww7. These paddocks also had the greatest masses of S in sediments, and water concentrations were also highest in paddocks ww4, ww6 and ww7. P. australis accumulated highest elemental mass than S. corymbosus, with the highest Zn mass of 93%. P. australis accumulated double the mass of U, Cu, Cl, Ca. In both plants, the roots consistently had highest elemental concentration with sequence often as follows roots> shoots> rhizomes. Sediment element mass accumulation of most tested elements significantly increased with depth, except for Zn and U, which decreased with depth. There are few significant differences in the mass distribution of the elements analysed between paddocks, which is assumed to reflect either the heterogeneity in the underlying sediments following construction of the wetlands, or lateral inputs into the system as seepage from other TSFs. Key words: AMD, Wetland, Varkenslaagte Canal, West Wits Mining Operation, metals, sediment, S. corymbosus, P. australis, ICP-MS, XRF.
A dissertation is submitted as MSc research project in partial fulfilment of the requirements for the degree of Master of Science in the School of Geography, Archaeology and Environmental Studies. July 2016.
Keywords: Acid mine drainage; Constructed wetlands; Phytoremediation